Antimycobacterial evaluation, preliminary phytochemical and cytotoxicity studies of cassia petersiana - Mothupi, Ramokone Florah (My University, 2022)
This study aimed to investigate antimycobacterial and cytotoxic compounds from Cassia petersiana. Cassia petersiana was selected for the current study based on its traditional use for treating tuberculosis (TB) symptoms. Extraction is an important step in the use of medicinal plants; hence, solvents of varying polarity were employed to extract a wide range of compounds where chloroform was the best extractant (67 mg). As there is no relation between the amount of plant material extracted and the bioactivity of the extracts, standard tests were used to determine the presence of different phytochemical constituents from Cassia petersiana and the total phenolic, flavonoid, and tannin contents were quantified using colorimetric assays. It was revealed that all the tested phytochemical constituents were present, and it was proven that phenolic compounds were the most abundant, followed by the tannins, while the flavonoids were the least among the common phytochemical constituents quantified. The phytochemical compounds were further profiled on thin-layer chromatography (TLC) and developed in BEA, CEF, and EMW solvent systems. Colourful compounds which indicated diverse phytochemicals were visualised with both vanillin-sulphuric acid and ultraviolet light on the phytochemical chromatograms and good separation of the compounds was from the BEA solvent system. The qualitative and quantitative antioxidant activity and antimycobacterial activity assays were used to evaluate the extracts from Cassia petersiana. Minimal antioxidant activity was observed on the qualitative antioxidant activity profile. These findings correlated with the minimal quantity of antioxidants from extracts of Cassia petersiana from the quantitative antioxidant assays; ferric reducing power and DPPH scavenging activity assays. Cassia petersiana extracts had bioactivity against Mycobacterium smegmatis as indicated by the lowest MIC value. The cell viability effects of the acetone crude extract from Cassia petersiana were evaluated against the tryptophan hydroxylase-1 (TPH-1) macrophage cells. Large scale extraction procedure was employed to extract a sufficient amount of plant material in preparation for the isolation of the bioactive compound. Bioassay-guided fractionation combined with column chromatography and TLC were used to isolate and purify the bioactive compound from the n-hexane extract of Cassia petersiana. The purified isolated compound was elucidated as β-sitosterol, which showed remarkable bioactivity against Mycobacterium smegmatis only on the TLC-bioautographic assay, while the quantitative antimycobacterial activity was higher xx with the MIC value of 2.5 mg/mL. Although β-sitosterol is known as a good antioxidant, it showed no antioxidant activity on the qualitative antioxidant activity assay. Therefore, further studies, including in vivo assay, are recommended on the isolated compound to evaluate its biological activities before consideration of its use in the development of alternative drugs.
Thesis (M.Sc.(Microbiology)) -- University of Limpopo, 2022
Keywords: Antimycobacterial and cytotoxic compounds; Cassia petersiana; Tuberculosis treatment; Medicinal plants; Medicinal plants -- Biotechnology; Tuberculosis -- Alternative treatment; Mycobacterial diseases